The Influence of Collateralizable Assets, Firm Size, Managerial Ownership, andInvestment Opportunity on Dividend Policy - Lestari, Wiwik Dwi (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This study aims to analyze the influence of Collateralizable Assets, Firm Size, Managerial Ownership, andInvestment Opportunity on Dividend Policy in LQ45 Index companies listed on the Indonesia StockExchange (IDX) from 2019 to 2023. Collateralizable Assets are proxied by COLLAS, Firm Size by SIZE,Managerial Ownership by MOWN, and Investment Opportunity by MVE/BE. Dividend Policy is proxied bythe Dividend Payout Ratio. The sampling technique employed in this research is purposive sampling,resulting in a final sample of nine LQ45 Index companies listed on the IDX. The study utilizes secondarydata obtained from the official IDX website. This research adopts a descriptive quantitative approach withmultiple linear regression analysis. The results indicate that the Collateralizable Assets variable has asignificance value of 0.009, and the Firm Size variable has a significance value of 0.001, suggesting thatCollateralizable Assets and Firm Size have a significant negative effect on Dividend Policy. Meanwhile, theManagerial Ownership variable has a significance value of 0.067, and the Investment Opportunityvariable has a significance value of 0.253, indicating that neither Managerial Ownership nor InvestmentOpportunity significantly affects Dividend Policy. However, simultaneously, Collateralizable Assets, FirmSize, Managerial Ownership, and Investment Opportunity collectively have a significant effect on DividendPolicy.